In vitro biological activities of different extracts from alcea dissecta - TAŞKIN, TURGUT; DOĞAN, AHMET (My University, 2022)
Objective: Alcea genus belongs to Malvaceae family and this genus is represented by 85 taxa in the world and 21 taxa in the Flora of Turkey. The flowers of Alcea genus contain plenty of mucilage and are used for the treatment of respiratory diseases such as asthma and cough. Alcea dissecta is known as ‘Govik, Hiro, Hero’ in Turkey, and the flowers and leaves of this species have been used in the treatment of asthma, injury, colds, and gastrointestinal diseases in Turkey. To the best of our knowledge, there is no report on the effect of extraction methods on the biological activity of this plant. In addition, although this species is being used as a medical plant, there is no study of the antioxidant, antiurease, esterase, and anticholinesterase activity of the plant. Therefore, the aim of this study was to evaluate in vitro antioxidant, anti-urease, esterase, anticholinesterase activities of Alcea dissecta using a variety of extracts. Methods: The antioxidant activities of different extracts were examined by DPPH, ABTS, FRAP, and CUPRAC methods. The total phenolic compounds contained in the extracts were determined using the Folin-Ciocalteu reagent (FCR) method. Anti-urease and anticholinesterase activities of different extracts were evaluated by indophenol and Ellman methods respectively. In addition, esterase activities of plant extracts were determined. Results: In the present study, ethanol:water (1:1, v/v) and chloroform extracts obtained maceration method showed stronger DPPH and ABTS radical scavenging activity than other extracts. The chloroform extract obtained Soxhlet method was found to have higher FRAP and CUPRAC values than other extracts. It was also found that the ethanol extract obtained maceration method showed the most potent anti-urease and anticholinesterase activity. According to the results, the strongest inhibitory effect on both hCA I and II isoenzymes was shown by the petroleum ether extract obtained Soxhlet method. Conclusion: As a result, it was determined that different plant extracts have antioxidant, anti-urease, esterase, anticholinesterase activities. In addition, the data obtained from this study will shed light on future research on the biological activities of this species.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Reviews and References (medical); Research and Theory; Alcea dissecta; biological activity; medicinal plant; ANHYDRASE INHIBITORY PROPERTIES; CARBONIC-ANHYDRASE; ANTIOXIDANT ACTIVITY; HELICOBACTER-PYLORI; MEDICINAL-PLANTS; ACETYLCHOLINESTERASE; DERIVATIVES; CAPACITY; FLOWER; Alcea dissecta; biological activity; medicinal plant